The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2014
DOI: 10.1155/2014/718084
|View full text |Cite
|
Sign up to set email alerts
|

High Resolution Melting Analysis for Rapid Mutation Screening in Gyrase and Topoisomerase IV Genes in Quinolone-ResistantSalmonella enterica

Abstract: The increased Salmonella resistance to quinolones and fluoroquinolones is a public health concern in the Southeast Asian region. The objective of this study is to develop a high resolution melt curve (HRM) assay to rapidly screen for mutations in quinolone-resistant determining region (QRDR) of gyrase and topoisomerase IV genes. DNA sequencing was performed on 62 Salmonella strains to identify mutations in the QRDR of gyrA, gyrB, parC, and parE genes. Mutations were detected in QRDR of gyrA (n = 52; S83F, S83Y… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
5
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 28 publications
1
5
0
Order By: Relevance
“… 47 , 50 Moreover, most of the isolates had an additional Asp87Asn mutations in gyr A (88.9%) and Ser80Ile mutation in par C (77.8%), which is associated with high level of ciprofloxacin resistance. 51–53 Similar mutations were also reported by Al-Marzooq et al, 54 Ngoi et al, 55 Zeng et al, 56 and Guimarães et al 57 On the other hand, the identified mutations are different from those observed by Azargun et al 58 Resistance of Enterobacteriaceae to quinolones have been reported with alterations in genes other than the gyr A and par C. Lindbäck, Rahman, Jalal, Wretlind 59 and others have related mutation in gyr B and par E to resistance to quinolones. 60 No other mutations were observed in par C, however, other investigators have reported a Glu84Val substitution as the most common mutation in the par C gene.…”
Section: Discussionsupporting
confidence: 81%
“… 47 , 50 Moreover, most of the isolates had an additional Asp87Asn mutations in gyr A (88.9%) and Ser80Ile mutation in par C (77.8%), which is associated with high level of ciprofloxacin resistance. 51–53 Similar mutations were also reported by Al-Marzooq et al, 54 Ngoi et al, 55 Zeng et al, 56 and Guimarães et al 57 On the other hand, the identified mutations are different from those observed by Azargun et al 58 Resistance of Enterobacteriaceae to quinolones have been reported with alterations in genes other than the gyr A and par C. Lindbäck, Rahman, Jalal, Wretlind 59 and others have related mutation in gyr B and par E to resistance to quinolones. 60 No other mutations were observed in par C, however, other investigators have reported a Glu84Val substitution as the most common mutation in the par C gene.…”
Section: Discussionsupporting
confidence: 81%
“…Mutations within QRDR of parC and parE genes were rarely detected and reported among Salmonella isolates [25] [31] [32]. The finding of double mutations in parE gene in this study are remarkable, and may be associated with higher level of FQ resistance [30] [31]. In addition to it, parE gene mutations were identified in three S. Enteritidis isolates that were having gyrA gene muta-tions too.…”
Section: Discussionmentioning
confidence: 51%
“…Previous research reported that the underlying mechanism for ciprofloxacin resistances may be caused by specific mutations in genes encoding DNA gyrase and topoisomerase IV that decrease quinolone sensitivity by weakening the interactions between quinolones and bacterial enzymes [ 27 ]. With the availability of WGS data and ResFinder’ sister database, PointFinder, two mutations were detected in gyrA (S83F and D87G) in strain SS20, confirming their associations with ciprofloxacin resistance [ 28 ].…”
Section: Discussionmentioning
confidence: 99%